An Introduction to the Level of Inquiry Model: Validity and Practicality of Inquiry STEM-Based Learning Sequence e-Worksheet to Stimulate Student Communication Skill - Rabbani, Ghani Fadhil; Abdurrahman, Abdurrahman; Maulina, Hervin; Herlina, Kartini; Haryanti, Septina Sri (STKIP Singkawang, 2024)
This study aims to describe an Inquiry-Based Learning (IBL) Sequence-based e-Worksheet with a valid STEM approach to stimulate students' communication skills in challenging learning through the Google Classroom platform and its practicality. The development research model is ADDIE, consisting of analysis, design, development, implementation, and evaluation stages. The data from this research are the results of validation and practicality, analyzed using mixed methods (quantitative and qualitative). The results of the data analysis show that the average e-worksheet validity is 3.77 in the very valid category, and the practicality proportion is 93.6% in the very practical category. Based on the results of data analysis, it can be concluded that; 1) an e-Worksheet based on an IBL Sequence with a valid STEM approach to stimulate students' communication skills in bold learning through the Google Classroom platform, which contains stages of IBL learning with a STEM approach containing activities that stimulate indicators of students' communication skills; and 2) Practicality of the IBL Sequence-based e-Worksheet with the STEM approach to stimulate students' communication skills in daring learning through the Google Classroom platform which is categorized as very practical, so that it can be used in high school Physics learning, class X odd semester, materials for Changing Straight Motion Order.